Formação de professores na Universidade Aberta do Brasil: discursos que governam - Osório, Mara Rejane Vieira (2010)
This study dealt with the analysis of discourses developed and implemented by the Open University of Brazil (UAB), with the intention to transform and modernize the brazilian teacher via distance education. The main objective of the research was to question, describe and analyze how the discourses of UAB and its priority Distance Education (EAD) act to transform teacher training, the teacher himself and what it means to be a teacher. This work is supported by theoretical focus came from elements of post-struturalist/foucauldian perspective that focuses on studies of governmentality. From this perspective, I propose to understand teacher training as a matter of government of teachers conducts, and UAB as a human technology, among others, developed to lead and manage part of this government. I observed the movement of two sets of UAB speeches: discourses presented in official documents and discourses of the Distance Bachelor in Mathematics Teaching (CLMD), one of the Federal University of Pelotas graduate courses. The following strategies were used for developing this study: analysis of official documents related to UAB and CLMD; analysis of teachers, students and manager of CLMD discourses and analysis of speeches presented in UAB events. I argued with this study, that the UAB (seen as general political discourse in the case of official speeches) produces a system of rationality that creates, directs, encourages and guides the direction of teacher training by distance education. In the case of CLMD (here, understood as a pedagogical practice of subjectivity), I have argued that the speeches focused on the Distant Education, and establish boundaries for constraining the government of teachers conducts, because they interfere in the way students act on themselves to produce their subjectivities.